Mindfulness Practices and Attention Control in Early Childhood and Primary Education: A Review - Jarar, Syeda Parsa; Widyasari, Pratiwi (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
Mindfulness-based interventions (MBIs) have gained recognition for enhancing attention control in early childhood education, helping students sustain focus, filter distractions, and regulate cognitive effort. While previous research highlights short-term benefits, gaps remain regarding long-term effectiveness, real-world implementation, and comparative efficacy against other attention-enhancing strategies. This review synthesizes findings on the impact of mindfulness on sustained, selective, and executive attention, bridging the gap between controlled experiments and classroom applications. A narrative review approach was employed, analysing peer-reviewed studies published between 2013 and 2024 from Medline, Google Scholar, ERIC, PsycINFO, and Scopus. Studies were selected based on predefined criteria; prioritizing research conducted in early educational settings. Findings indicate that mindfulness strengthens neural pathways related to executive function, leading to improved focus, impulse control, and cognitive flexibility. Programs like the Mindful Schools Curriculum and Kindness Curriculum have demonstrated positive effects, yet barriers such as teacher training gaps, limited classroom time, and intervention variability hinder widespread adoption. This review emphasizes the need for longitudinal studies, cross-cultural comparisons, and the integration of digital mindfulness tools. While mindfulness offers promise as an educational strategy, further research is required to assess its scalability and long-term impact on attention control and learning outcomes.